Gold nanoparticle printed coverslips to facilitate fluorescence-TEM correlative microscopy. (23rd November 2017) - Prabhakar, Neeraj; Määttänen, Anni; Peltonen, Jouko; Hänninen, Pekka; Peurla, Markus; Rosenholm, Jessica M
Abstract : Gold nanoparticle patterns inkjet-printed on glass coveslips have high contrast in reflection mode of fluorescence microscopy, under stereo microscope in embedding the cells for transmission electron microscopy, and in the polymerized block face, facilitating tracking of cells through different imaging modalities in correlative light and electron microscopy experiments. Abstract: Correlative light and electron microscopy (CLEM) allows combining the advantages of fluorescence microscopy and electron microscopy for cell imaging. Rare phenomenon expressing cells can be studied by specifically tagged fluorophores with fluorescence microscopy. Subsequently, cells can be fixed and ultra-structural details can be studied with transmission electron microscopy (TEM) at a higher resolution. However, precise landmarks are necessary to track the same cell throughout the CLEM process. In this technical report, we present a high contrast inkjet-printed gold nanoparticle patterns over commercial glass coverslip to facilitate cell tracking with correlative microscopy. High contrast and strong reflection from nano gold pattern can be used as a fixed landmark for cell identification with fluorescence microscopy. Nano gold printed letters over coverslips are visible in resin blocks, which can be further used to identify the cell of interest for performing sectioning of embedded cell blocks for TEM.